LINC01426 Triggers Growth and Metastasis of Lung Adenocarcinoma as a Prognostic Indicator. (17th May 2022) - Deng, Youjun; Cai, Songhua; Liu, Wenyi; Yang, Chenglin; Guo, Xiaotong
Abstract : The vital regulation of abnormally expressed lncRNAs in human cancers has been identified. This study is aimed at illustrating the role of LINC01426 in influencing malignant behaviors of lung adenocarcinoma (LUAD) and the possible mechanism. Differential expressions of LINC01426 in a downloaded profile containing LUAD and normal tissues were analyzed using Gene Expression Profiling Interactive Analysis (GEPIA) database and were reconfirmed in clinical samples collected in our hospital. In addition, LINC01426 level in lung carcinoma cell lines was detected by quantitative real-time polymerase chain reaction (qRT-PCR) as well. The relationship between LINC01426 expression and the age, tumor node metastasis (TNM) staging, lymphatic metastasis, tumor differentiation, and overall survival of LUAD was analyzed. After intervening LINC01426 level in H1299 and PC9 cells, proliferative and metastatic changes were assessed by functional experiments. LINC01426 was upregulated in LUAD tissues and cell lines. Its level was closely linked to TNM staging, lymphatic metastasis, tumor differentiation, and overall survival of LUAD. Knockdown of LINC01426 suppressed proliferative and metastatic abilities in H1299 and PC9 cells. LINC01246 is upregulated in LUAD samples and predicts a poor prognosis. It drives malignant process of LUAD via stimulating proliferative and metastatic abilities.